Understanding Questions and Concerns Regarding COVID-19 and the COVID-19 Vaccine Among Populations Presenting at a COVID-19 Vaccine Clinic Hub: A Qualitative Study - Hari N. Krishnakumar; Gretchel A. Gealogo; Taylor Holland; Monica Martinez; Lucas Hendrix; Michael Collins; Melissa Donate; Maryann England; Eric Kumana; Joshua Garcia; Andrew Wilkey; Niklesh Akula; et al. (SAGE Publishing, 2022)
Background: Skepticism among the public surrounding the COVID-19 vaccine is still prevalent despite vaccine-positive communication and many Americans having already received the vaccine. Side effects of the vaccine, as well as its expeditious research and development, are among the top concerns among those hesitant to receive the coronavirus vaccine. Moreover, there is additional concern regarding the association between comorbidities and severity of illness due to the coronavirus pandemic. Objective: We aimed to describe the pandemic- and vaccine-related concerns of South Texas residents who attended the UT Health San Antonio School of Nursing's vaccine clinic with the goal of better understanding vaccine-related misconceptions and hesitancy for subsequent vaccination campaigns and boosters. Methods: An electronic survey accessible via a QR code on printed flyers was distributed throughout the waiting areas and post-vaccine observation rooms within the COVID-19 vaccine clinic at UT Health San Antonio School of Nursing from April 5 to 16, 2021. The survey contained a primary open-ended question designed to obtain information on concerns of the clinic attendees regarding the COVID-19 pandemic and COVID-19 vaccine. A thematic analysis was performed on the qualitative data to identify major themes to better understand concerns of vaccine clinic visitors. Results: During the 11-day period, 510 attendees received vaccinations through the vaccination clinic and completed the survey. Five areas of concern were identified by the 277 attendees: immunity, future vaccinations, vaccine symptoms and safety, protocol post-vaccination, and child vaccinations. Post-hoc sentiment analysis showed that responses were generally neutral or negative. Conclusion: This study provides a perspective regarding questions and concerns of South Texas residents regarding the COVID-19 pandemic, the vaccine, and their general health status within a vaccinated population. Vaccine recipients were found to still have questions even after receiving the vaccine, suggesting that eliminating uncertainty surrounding the COVID-19 vaccine is not necessary to motivate individuals to receive the vaccine. Instead, addressing concerns through public health messaging could be a useful strategy to address vaccine-related concerns and increase subsequent vaccine uptake in future vaccination campaigns and boosters.